Bcl11b sets pro-T cell fate by site-specific cofactor recruitment and by repressing Id2 and Zbtb16. (December 2018) - Hosokawa, Hiroyuki; Romero-Wolf, Maile; Yui, Mary; Ungerbäck, Jonas; Quiloan, Maria; Matsumoto, Masaki; Nakayama, Keiichi; Tanaka, Tomoaki; Rothenberg, Ellen
Abstract Multipotent progenitor cells confirm their T cell–lineage identity in the CD4– CD8– double-negative (DN) pro-T cell DN2 stages, when expression of the essential transcription factor Bcl11b begins. In vivo and in vitro stage-specific deletions globally identified Bcl11b-controlled target genes in pro-T cells. Proteomics analysis revealed that Bcl11b associated with multiple cofactors and that its direct action was needed to recruit those cofactors to selective target sites. Regions near functionally regulated target genes showed enrichment for those sites of Bcl11b-dependent recruitment of cofactors, and deletion of individual cofactors relieved the repression of many genes normally repressed by Bcl11b. Runx1 collaborated with Bcl11b most frequently for both activation and repression. In parallel, Bcl11b indirectly regulated a subset of target genes by a gene network circuit via the transcription inhibitor Id2 (encoded byId2 ) and transcription factor PLZF (encoded byZbtb16 );Id2 andZbtb16 were directly repressed by Bcl11b, and Id2 and PLZF controlled distinct alternative programs. Thus, our study defines the molecular basis of direct and indirect Bcl11b actions that promote T cell identity and block alternative potentials. Bcl11b is needed to establish T cell–lineage identity. Rothenberg and colleagues provide a comprehensive analysis of Bcl11b–cofactor interactions and reveal the functional relevance of direct and indirect Bcl11b binding activity in thymocytes.